Assembly of Multi‐Phthalocyanines on a Porphyrin Template by Fourfold Rotaxane Formation. Issue 35 (15th July 2016) - Yamada, Yasuyuki; Kato, Tatsuhisa; Tanaka, Kentaro
Abstract: A stacked assembly composed of a porphyrin and two phthalocyanines was prepared through fourfold rotaxane formation. Two phthalocyanine molecules, bearing four 24‐crown‐8 units, were assembled onto a porphyrin template incorporating four sidechains with two dialkylammonium ions each through pseudorotaxane formation between crown ether units and ammonium ions. The Staudinger phosphite reaction, as the stoppering reaction, resulted in the formation of the stacked heterotrimer composed of a porphyrin and two phthalocyanines connected through a fourfold rotaxane structure. UV/Vis spectroscopic and electrochemical studies of the heterotrimer indicated that there is a significant electronic interaction between the two phthalocyanine units due to the close stacking. The electrochemical oxidation process of the stacked heterotrimer was studied by cyclic voltammetry and spectroelectrochemistry. Electron paramagnetic resonance (EPR) spectroscopy of a dinuclear Cu II complex, in which two Cu II phthalocyanines were assembled on a metal‐free porphyrin template, revealed that two Cu II phthalocyanines were located within the stacking distance, which resulted in an antiferromagnetic interaction between the two S = 1 / 2 spins in the ground state of the Cu 2+ ions in the heterotrimer. Abstract : Four wheel drive : Fourfold rotaxane formation was utilized to synthesize a supramolecular stacked assembly in which two phthalocyanines are assembled on a porphyrin template. The close stacking leads to a significant electronic interaction between the two phthalocyanine units.